STRATEGIC COMMUNICATION AND CHANGE MANAGEMENT IN THE HOSPITALITY INDUSTRY IN RIVERS STATE - Laguo Livingstone Gilbert; Lolo Teddy Adias (American Journals, 2025)
The hospitality industry in Nigeria, particularly in Rivers State, faces persistent volatility stemming from infrastructural deficits, security concerns, and evolving customer expectations. As a result, change management has become a vital organizational function, requiring not only strategic planning but also effective internal communication. This study investigates the role of strategic communication in facilitating successful change management within hospitality firms in Rivers State. Specifically, it examines how communication clarity, timeliness, channel appropriateness, and employee involvement influence employees’ readiness for change, resistance levels, and overall implementation outcomes. Adopting a quantitative research design, the study utilized a structured questionnaire distributed to a stratified sample of 173 employees from selected hospitality firms. A total of 142 valid responses were analyzed using SPSS Version 26. The findings revealed that all four dimensions of strategic communication significantly and positively predicted change management success, with employee involvement emerging as the strongest predictor (β = 0.318, p < 0.001). These results underscore the importance of participatory, timely, and clear communication practices in shaping employee support and aligning behavior with new organizational goals. The study concludes that strategic communication is not merely a supportive function but a critical enabler of organizational transformation in the hospitality sector. It recommends that hospitality managers institutionalize clear, responsive communication frameworks and prioritize employee engagement throughout the change process to enhance adaptability, minimize resistance, and ensure more sustainable change outcomes in a rapidly evolving industry environment.
Keywords: Change Management, Employee Involvement, Hospitality Industry, Strategic Communication